UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA POKOK BAHASAN SEGIEMPAT DAN SEGITIGA MELALUI STRATEGI LATIHAN BERJENJANG DENGAN DUKUNGAN MEDIA GAMBAR DI KELAS VII MTs. CERDAS MURNI TEMBUNG TAHUN PELAJARAN 2014/2015 - Dewi Astuti (AXIOM : Jurnal Pendidikan dan Matematika, 2016)
The problems will be explain in this research is the decrease of resultstudy students' in Class VII MTs Cerdas Murni Tembung on thesubject of Square and triangles. This is evident from an unqualifiedstudents solve problems Square and triangles, so that the necessaryeffort and appropriate learning models to overcome the problems.Thepurpose this study is to know the increase in students' mathematicslearning outcomes by using a tiered training strategies and with thesupport of media animation pictures on the subject of square andtriangles in class VII MTs Cerdas Murni Tembung. This research wasmeasures class research. The subject in this research were studentsClass VII MTs Cerdas Murni Tembung as many as 40 students,consisting of 20 people male students and 20 female students. Thisresearch was conducted by 2 cycles in four meetings, which consists offour stages: planning, action, observation, and reflection . for see andknow the capabilities of students, research using observation sheetstudent activity, questions about the pretest and post test form multiplechoice given to all students to answer them individually. Based on theresults of initial tests before being given action shows the percentage ofclassical learning completeness amount of 7,5% (3 students) .Aftergiven instruction action using a tiered training strategies and with thesupport of media animation computer. Completeness percentageobtained in the first cycle of 42.5 % ( 17 students ) . After repairs in thefirst cycle to second Cycle reach percentage rate becomes 87.5 %% (35 students). So as to obtain an increase in students' mathematicslearning outcomes of the first cycle second cycle reached 45% .Basedon the above results, it can be concluded the application of learning byusing a tiered excercise Strategist and with the support of media imagescan improve learning outcomes math on the subject of Square andtriangles.